Hyperspectral Irradiance Data for a Comparison and an Analysis of Optical Satellite Spectral Observation: Based on Seogwipo Forest Flux Tower - Hongtak Lee; JongMin Yeom (Geo Data, 2019)
Comparison with ground-truth data is essential for developing and applying remote sensing algorithm towards the Earth surface. Unfortunately, major sources of domestic ground-truth data are depending on field-campaign with limited period because of insufficient all-time observation facilities within a domestic region. Korea Aerospace Research Institute, KARI, is planning to construct and operate surface observation tower to provide remote sensing infrastructure. This study was conducted as a pilot program of the observation tower construction and targeted to observe surface reflectance. The observation was made for about 21 months from May 2017. Two hyper-spectroradiometers were installed on top of a forest flux tower at Mt. Halla to measure hyperspectral up/down-welling irradiance, and surface reflectance was derived simply from their ratio. The derived surface reflectance was compared to surface reflectance values estimated from LANDSAT8 VNIR images, and the two surface reflectances coincided while showing effectiveness of the derived surface reflectance. The data acquired from this study would be able to provide background information for the expected surface observation tower, as well as actual ground-truth data for remote sensing application upon Mt. Halla area.